FRI0358 ROLE OF MIRNA-21-5PAS A POTENTIAL BIOMARKER FOR THE INFLAMMATION PATHWAY IN PSORIATIC DISEASE AND RESPONSE TO METHOTREXATE TREATMENT. (June 2019) - Machhar, Rohan; Pollock, Remy; Ye, Justine; Chandran, Vinod; Gladman, Dafna D.
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory arthritis occurring in patients with psoriasis. Several studies have shown links between altered miRNA expression with the pathogenesis of several autoimmune disorders. We previously demonstrated that miR-21-5p was upregulated in PsA compared to psoriasis without arthritis (PsC) and healthy controls (HC) and is thus a potential biomarker for PsA. Objectives: 1) To determine whether miR-21-5p is differentially expressed in PsC patients who convert to PsA vs non-convertors and validate the previous results in an independent cohort. 2) To determine the role of miR-215p in the response to methotrexate treatment (MTX) 3) To determine whether miR-21-5p modulates inflammation in psoriatic disease. Methods: Serum & whole blood RNA samples were collected from 54 convertors and 54 non- convertors (matched for age, sex, psoriasis duration), 40 patients with early PsA (<2 years' disease duration and not receiving biologic therapy), 40 patients with PsC (>10 years disease duration, not receiving biologic therapy, and matched to PsA patients on age, sex, psoriasis duration, and age of psoriasis onset), and 40 HC (matched to patients based on age, sex). RNA was extracted using the Tempus Spin RNA Isolation Kit. miR-21-5p was validated using droplet digital PCR (ddPCR). Serum Il-17, CXCL10, IL-23, TGFβ1 were measured by commercially available ELISA kits. Mann- Whitney test, Kruskal-Wallis test, Wilcoxon signed rank test and Spearman correlations were performed. Results: The expression of miR-21-5p was significantly higher in convertors compared to non-convertors (Fold change(FC)=2.16, p=0.002). miR-21-5p was upregulated in PsA compared to PsC (FC=2.32, p=0.001) and HC (FC=15.7, p=<0.0001) in the validation cohort. miR-21-5p was significantly down regulated 24 weeks post-MTX treatment in 30 PsA patients (FC=1.9, p< 0.008), which correlated with swollen (r=0.49, p=0.003) and tender joint counts (r=0.41, p=0.02) supporting a possible role in inflammation pathway in PsA patients. IL-17 levels in PsA & PsC were significantly higher from HC (p= 0.03), but not different between PsA & PsC. IL-17 levels were down- regulated post MTX treatment and correlated with miR-21-5p (r=0.56, p=<0.001), CXCL10 levels (r=0.48, p=0.01), IL-23 levels (r=0.43, p=0.02), TGFβ1 (r= -0.45, p=0.04) and total active joint counts (r=0.40, p=0.016). Conclusion: Up regulated expression levels of miR-21-5p in convertors and in PsA patients suggests a role as a potential biomarker for PsA. In the presence of upregulated miR-21-5p, IL-17 and IL-23 are upregulated while TGFβ1 is down regulated. When miR-21-5p is decreased IL-17 and IL-23 downregulate, with up regulation of TGFβ1. We have thus determined the role of miR21-5p as a potential biomarker for inflammation pathway in psoriatic disease and response to MTX possibly through modulation of CXCL10 and IL-17/IL-23 axis. Disclosure of Interests: Rohan Machhar: None declared, Remy Pollock: None declared, Justine Ye: None declared, Vinod Chandran: None declared, Dafna D Gladman Grant/research support from: AbbVie, Amgen, Celgene, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead, Janssen, Lilly, Novartis, Pfizer, and UCB